Lasers in Orthodontics – A Review - Mote, Nilesh; Toshniwal, N G; Mani, Shubhangi; Nalkar, Ashwini; Dhanjani, Vishal (Orthodontic Journal of Nepal, 2020)
Introduction: In past few years, there is huge improvement in orthodontics. Different innovation in orthodontics made the procedure easier and less time consuming. Application of laser is one of them. Many types of dental lasers are currently available that can be efficiently used for soft and hard tissue applications in the field of orthodontics. Two types of lasers are there. One is hard tissue laser, and another is soft tissue laser. Laser therapy is advantageous because it often avoids bleeding, can be pain free, is non‑invasive and is relatively quick. The high cost is its primary disadvantage. The purpose of this article is to provide an overview regarding safe and proper use of soft-tissue lasers in orthodontics